Analysis of financial inclusion indicators FINDEX - a study of a group of Arab countries- - Zebiri, Noura (Finance and Business Economies Review, 2022)
This research paper aimed to address the reality of financial inclusion in the Arab countries, by analyzing the most important indicators of financial inclusion for a group of Arab countries. In order to answer the problem of the study, and achieve its objectives, Using the descriptive method and the analytical method, using the descriptive method. The study found many results, the most important of which is the decline in financial inclusion indicators in the group of Arab countries under study, with the exception of the United Arab Emirates, for each of the bank account ownership with official financial institutions, the index of access to financial and banking services and products and the index of digital financial services, as recommended The study stressed the need to intensify the financial, legislative and legal efforts of the group of Arab countries under study in order to enhance the process of financial inclusion in them